Rancang Bangun Sistem Simulasi Pengajuan Kredit dan Company Profile PT. BPR Arsham Sejahtera Menggunakan Metode WDLC - Maria Meiliani Kezia; Shumaya Resty Ramadhani (ABEC Indonesia, 2023)
People Economic Bank (BPR) Arsham Sejahtera is one of the banks that serve conventional business activities. As information and communication technology develops, system requirements become integral to company’s business. Company information and credit simulations submitted through the system can be conveyed, considering that the side can be accessed by users. The system that owned system is still unable to work optimally, resulting in several pages not appearing when clicked and making users feel that the system quality accordance with the desired expectations. So it is necessary to design a system by modifying the system to facilitate the dissemination of company information. This system uses PHP as the programming language with the CodeIgniter framework and MySQL as the database. Then, this system uses a software development method in the form of the Web Development Life Cycle (WDLC) to collect user requirements until implementation and maintenance. Based on SUS to test, there is an average value of 91,38%, indicating that the system is successfully used by management and the community. Then the system can be used to convey company information and simulate credit applications.